Development of biodegradable membranes for the delivery of a bioactive chitosan‐derivative on cartilage defects: A preliminary investigation. Issue 7 (27th March 2020) - Scognamiglio, Francesca; Travan, Andrea; Borgogna, Massimiliano; Donati, Ivan; Marsich, Eleonora
Abstract: Biodegradable membranes for cartilage applications were manufactured starting from polymeric networks of a lactose‐modified chitosan (CTL), previously proposed for chondrocytes stimulation. This implantable biomaterial was conceived as a reservoir of a bioactive polymer that could promote the activity of chondrocytes and the healing of cartilage defects. Freeze‐drying of reticulated hydrogels enabled to obtain pliable membranes with a homogeneous polymeric texture, as pointed out by scanning electron microscopy analyses. Swelling tests and dimensional evaluations showed that the material is able to absorb physiological fluids and expand gradually upon rehydration. This feature was evaluated on a simulated cartilage defect on pig's humerus (ex vivo), which revealed the capability of the membranes to progressively fit the tissue voids on the damaged cartilage. The rheological properties of the rehydrated membranes pointed out their peculiar strain‐stiffening behavior, which represents a promising feature for the regeneration of tissues subjected to variable mechanical loads and deformations. Biological in vitro studies demonstrated the biocompatibility of the membranes in contact with primary chondrocytes and osteoblasts. Taken together, these results represent a starting point for the development of a novel generation of implantable biomaterials for cartilage treatment based on CTL.